Mathematics teachers’ professional knowledge - Ponte, João Pedro da (1994)
This paper addresses the study of teachers’ knowledge, beliefs, conceptions and practices, presenting some illustrations from the area of problem solving. In mathematics education, the teacher has attracted much less work than the student. This may be due, in part, to the different knowledge base of interest in each case. Regarding students, we are concerned with their learning of mathematics. The nature of mathematical knowledge is itself problematic, yet that does not seem to raise too many difficulties for our work. Regarding teachers, it is much less clear what is the specific knowledge (nec-essary for teaching mathematics) that we should be looking at. Is it knowledge of math-ematics content? Of mathematics pedagogy? Of students’ cognitive processes? Some mixture of several of these? In the first part of the paper I will briefly review work done on teachers’ professional knowledge and related concepts within and outside PME. Then, I will present cases taken from empirical research and discuss a few concepts used in our investigations. And in the final part I will contrast some general frameworks to study mathematics teachers’ professional knowledge and draw some perspectives for future work.